COVID-19 and English council funding: How are budgets being hit in 2020-21? - Kate Ogden; David Phillips (Institute for Fiscal Studies (IFS), 2020)
The public health and economic effects of the COVID-19 crisis are creating a perfect storm for councils' finances, simultaneously increasing spending and reducing incomes. For example, personal protective equipment (PPE) and social distancing requirements have increased unit costs for a range of services, and most notably adult social care, where many service users are particularly vulnerable to the health effects of COVID-19. Councils are taking on additional responsibilities to house rough sleepers, support those shielding at home, and help with the testing, tracing and control of COVID-19 outbreaks. And the wider economic effects of the crisis are hitting councils' various income sources to different extents as households and businesses radically change their behaviour and struggle to pay tax bills, rents and service charges. Building on previous work by researchers at IFS on the financial risk and resilience of different councils and by the Local Government Association (LGA) on councils' own expectations of the financial impact of the COVID-19 crisis as reported to the Ministry of Housing, Communities and Local Government (MHCLG), this report: examines the scale and nature of forecast impacts on spending and income from sales, fees and charges (SFCs) and commercial and other sources; explores how impacts may vary across council types, regions and council characteristics; compares the impacts with the financial resources provided to councils by central government and with the resources available to them in the form of reserves; considers the implications for future funding policy.
Keywords: 330; Gesundheitsversorgung; Öffentliche Finanzen; Coronavirus; Wirkungsanalyse; Großbritannien